Overweight and obesity among children and adolescents in Bangladesh: a systematic review and meta-analysis. (January 2017) - Biswas, T.; Islam, A.; Islam, Md.S.; Pervin, S.; Rawal, L.B.
Abstract: Objectives: The increasing prevalence of overweight and obesity among children (0–12 years) and adolescents (13–19 years) has emerged as a major public health threat in Bangladesh. Unfortunately, there is a serious paucity of credible data on these issues that can be used for policy and programmatic development. This article presents a systematic review of studies on overweight and obesity to present a more accurate estimate by pooling results. Study design: Systematic review. Methods: The study systematically reviewed relevant literature published between 1998 and 2015 using predefined inclusion/exclusion criteria. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist was used to identify relevant studies. Measures of heterogeneity and variability were calculated, and a random effect model was used to report pooled prevalence rates of overweight and obesity. Results: The findings show that prevalence rates of overweight and obesity among children and adolescents varied widely from 1.0% to 20.6% and 0.3% to 25.6%, respectively. The pooled prevalence rates of overweight and obesity were 7.0% (95% confidence interval [CI] 5.0–10.0) and 6.0% (95% CI 4.0–8.0), respectively. The pooled prevalence rate of overweight increased substantially over the years, from 3.6% during 1998–2003 (95% CI 0.3–29.2) to 5.7% during 2004–2009 (95% CI 0.8–30.2) and 7.9% by 2010–2015 (95% CI 5.1–12.1). However, the pooled prevalence rate of obesity registered a sharp decline between 1998–2003 and 2004–2009 – from 9.7% (95% CI 5.7–16.2) to 2.0% (95% CI 0.3–11.1) – and subsequently increased significantly to 9.0% by 2010–2015 (95% CI 5.3–14.6). Conclusions: This review identified increasing trends in the prevalence of overweight and obesity among children and adolescents in Bangladesh. This study underscores the urgent need to promote healthy lifestyles among children and adolescents with a view to effectively address the increasing problem of overweight and obesity. This would also help to prevent the development of chronic non-communicable diseases in adulthood. Highlights: Childhood obesity as a major public health threats in Bangladesh. Findings show the increasing patterns of overweight and obesity over the past 15 years. Need to promote healthy lifestyles among children and adolescents.